Impact of Groundstrap Configuration on Exhaust Emissions in 110cc Motorcycles: The Role of Electrode Material and Coil Turns - khambali khambali; Vinan Viyus (PT. ELSHAD TECHNOLOGY INDONESIA, 2025)
Environmental concerns regarding emissions from small motorcycles necessitate the optimization of ignition systems to improve combustion efficiency and reduce harmful exhaust gases. This study analyzes the combined effect of groundstrap configuration—specifically coil turns and material type (copper vs. aluminum)—on exhaust emissions (CO, HC, CO₂, and O₂) in a 110cc motorcycle. The experimental approach involved testing a 110cc four-stroke motorcycle with copper and aluminum groundstraps. The number of coil turns was varied (100, 150, and 200 turns), and engine speeds (1400, 2000, 4000, and 6000 rpm) were tested. Emissions were measured using a calibrated gas analyzer. Results revealed that copper groundstraps with 200 turns significantly reduced CO and HC emissions, with the most notable CO reduction. Copper groundstraps were superior in stabilizing ignition voltage, improving combustion quality compared to aluminum. In contrast, while aluminum groundstraps showed lower emissions, they were still effective at higher engine speeds. This study demonstrates that copper groundstraps with optimal coil turns effectively reduce harmful emissions and improve combustion in small motorcycles, offering a pathway to more environmentally friendly ignition systems.